Potential of Multientomopa Streptomyces sp. and Tripchoderma sp. in Potato Extract Broth and Glucose Nitrate Broth Media on Pests (Spodoptera litura) Eating Behavior by in Vitro Test - Ika Nur Fitriana; Penta Suryaminarsih; Tri Mujoko (Nusantara Science and Technology Proceedings)
Streptomyces sp. and Trichoderma sp. are biological agents that have high potential to produce secondary metabolites to reduce losses of agricultural products caused by pests. This study aims to determine the multientomopathogenic potential of Streptomyces sp. and Trichoderma sp on EKG and GN media on feeding behavior of Spodoptera litura pests in vitro. 10 S. litura (2nd instar) were placed in a box then the larvae with each entomopathogenic treatment. Besides, feed as much as 5 grams for each box every day for 7 days. Observations were made by weighing the difference in daily feed weight for 7 days. Effect of treatment on feeding activity of Spodoptera sp. on the 7th day after application showed that EKGST 5: 1 treatment had the highest value due to the activity of the chitinase enzyme from Streptomyces sp. and Trichoderma sp. Calculation of the ability of chitin hydrolysis by the enzyme chitinase is done by calculating the diameter of the clear zone that is formed then reduced by the diameter of the blotting paper containing supernatant secondary metabolites. Chitinase testing was carried out to determine the ability of secondary metabolites produced by Streptomyces sp. and Trichoderma sp. in hydrolyzing chitin. The widest zone is produced by multientomopathogenic Streptomyces sp. and Trichoderma sp. in EKGST 5: 1 treatment 3cm. Damage to the digestive tract due to the chitinase enzyme causes a decrease in the ability to absorb nutrients that have an impact on the reduced activity of Spodoptera litura.